2020
DOI: 10.3390/polym12010223
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Montmorillonite and 3YSZ as the Inorganic Fillers in Fluoride-Releasing and Rechargeable Dental Composition Resin

Abstract: Dental caries (tooth decay) is the most frequent oral disease in humans. Filling cavities with a dental restorative material is the most common treatment, and glass ionomer cements are the main fluoride ion release restorative materials. The goal of this study was to develop a restorative compound with superior fluoride ion release and recharge abilities. Previously developed fluorinated bentolite and hydrophobized 3YSZ were used as two different inorganic fillers mixed in a bisphenol A-glycidyl methacrylate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Analysis showed that this was caused by the stretching vibration of the carbonyl group at 1719 cm −1 and the stretching vibration of C-H on saturated carbon at 2945 cm −1 . Both the carbonyl group and the C-H group are groups of TXA, indicating that TXA reacted with montmorillonite to form a new product [37][38][39]. The interlayer of montmorillonite was combined by van der Waals force, and the many metal cations and hydroxyl hydrophilic groups in the montmorillonite cell thus showed strong hydrophilicity, and water molecules could enter the interlayer, causing the interlayer spacing (d001) to increase, resulting in the expansion of montmorillonite.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis showed that this was caused by the stretching vibration of the carbonyl group at 1719 cm −1 and the stretching vibration of C-H on saturated carbon at 2945 cm −1 . Both the carbonyl group and the C-H group are groups of TXA, indicating that TXA reacted with montmorillonite to form a new product [37][38][39]. The interlayer of montmorillonite was combined by van der Waals force, and the many metal cations and hydroxyl hydrophilic groups in the montmorillonite cell thus showed strong hydrophilicity, and water molecules could enter the interlayer, causing the interlayer spacing (d001) to increase, resulting in the expansion of montmorillonite.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fluorinated MMT (F-MMT) could act as a filler for the polymer matrix and as a source of fluoride ions for targeted release [85][86][87]. Recent studies have successfully demonstrated that F-MMT incorporated into a resin matrix (acrylamide) can achieve a desirable sustained release of fluoride and dual fluoride release mechanism [17,50]. The material developed showed great potential for application in dentistry as a pit and fissure sealant.…”
Section: Fluoride Substituted Montmorillonitementioning
confidence: 99%
“…The lattice structure of the alternating tetrahedral sheets and octahedron sheets is shown in figure 1(B). Outside of dentistry, MMT has attracted interest in various fields, including reinforcing ceramics, improving polymer composites, as a crucial organic catalyst, and in medical and pharmaceutical applications [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This material is proven to have anti-plaque effect, reducing the adherence of harmful bacteria to the tooth structure, is adequate for the treatment of hypersensitivity and non-cytotoxic to human teeth [6]. Appling PRG-technology to the filler in resin based composite materials gives them bioactive properties through fluoride release and recharge, similar to traditional glass-ionomers, but maintaining in the same time physical and esthetical properties of the composites [7,8].…”
Section: Introductionmentioning
confidence: 99%